A padronização de fases internas do procedimento licitatório na modalidade pregão, na forma eletrônica, dentro do sistema de compras da UTFPR - Tosawa, Silvio Hideo (2019)
The public administration system of acquisiton must always seek to satisfy society´s interests, based on transparency about the utilized resources, thus being necessary the usage of new management models. The electronic auction, a modality of auctioning subject to Law 10.520, from July, 17th, 2002, came in activity due to the necessity for higher competitiviness, transparency and accountability on public bidding processes. This study aims at creating a standard structure for formalizing the internal phases of the bidding processes, in its electronic form, at UTFPR. A way to integrate efficiency and celerity in the bidding processes was sought in order to ensure the realization of coherent and even procedures, that would, in their time, reach the goals created by the managerial administration in the early 1990´s. The bidding processes from years 2014-2018 showed operational inconsistencies that made UTFPR´s acquisition system highly time-consuming. Therefore, a new checklist of procedures, showing only UTFPR´s acquisition department deeds, was presented as a result.